2013
DOI: 10.22401/jnus.16.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnetized Water on Histological Structure of Heart, Lung and Spleen of Albino Rats

Abstract: The aim of the study was to investigate the effect of magnetized water on the histological structure of heart, lung and spleen. For this purpose, twenty five albino rats were divided into five equal groups, the first group was considered as control group. The other groups were given magnetized water with intensity of 250, 750, 1000, 1500 gause every day for 30 days. Then the animals were sacrificed and the histological change on heart, lung and spleen was studied. Histopathology of heart in rats treated with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our current study displays that nephrotoxicity induced by diabetes could be rescued by the treatment with Ginkgo biloba extract and magnetized water. Likewise, a concomitant reduction in nephrotoxic effects after Ginkgo biloba treatment was mentioned before [ 14 16 , 31 34 ] as well as magnetized water treatment [ 19 , 21 , 25 27 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our current study displays that nephrotoxicity induced by diabetes could be rescued by the treatment with Ginkgo biloba extract and magnetized water. Likewise, a concomitant reduction in nephrotoxic effects after Ginkgo biloba treatment was mentioned before [ 14 16 , 31 34 ] as well as magnetized water treatment [ 19 , 21 , 25 27 ].…”
Section: Discussionmentioning
confidence: 89%
“…Water was pumped through a flexible tube by a water pump installed inside the unit. The produced magnetic strength was 600 Gauss (measured by a WT10A Tesla meter), which is an average value of the magnetic field strength used in experimental animals and proved to have no pathological effect [ 27 ]. The used magnetic field was uniform and perpendicular to the water flow.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations on the histological effects of magnetized water to animals appears to be limited, however, in one study it was shown that rats drinking magnetized water at 0.075 or 0.10 T showed hyperplasia of the lymphoid tissue while the highest tested level of 0.15 T led to necrosis of this tissue (Al‐Saffar et al, ). A possible cause for hyperplasia and necrosis was suggested to be an interference of cellular communication and DNA damage, respectively (Al‐Saffar et al, ; Kamarudin, Sulaiman, & Ismail, ). Another possibility could include compromising the integrity of the cellular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Water flow was at a relatively low speed (0.34 L/min) to avoid overflow. The 600G is an average strength that has been tested to cause no pathological lesions in experimental rats 26…”
Section: Methodsmentioning
confidence: 99%